Job Satisfaction of Freelance Photographers: The Role of Self-Efficacy and Job Characteristics - Erni Prasetyo; Sulastri Irbayuni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of self-efficacy and job characteristics on the job satisfaction of freelance photographers in Surabaya. The background of this research is based on the growth of the gig economy, which has encouraged the emergence of independent work patterns where workers have the freedom to manage their own time, methods, and projects. However, this freelance work system also presents various challenges, such as project uncertainty, fluctuating workloads, and limited structured support or evaluation. In the context of freelance photography, these dynamics are particularly evident, as the work demands not only creativity but also managerial skills to organize work processes independently. This study employs a quantitative approach using a survey method with questionnaires distributed to 100 freelance photographers selected through purposive sampling. Data were analyzed using the Partial Least Squares (PLS) method. The results indicate that self-efficacy and job characteristics significantly contribute to shaping job satisfaction. Strong self-efficacy particularly previous work experience enhances freelancers’ confidence in facing challenges, while clear job characteristics, especially in terms of task identity, make them feel more directed, valued, and satisfied with their work. These findings emphasize the importance of both internal and external factors in determining job satisfaction and provide theoretical as well as practical contributions to the management of freelance workers in the creative sector, particularly in designing adaptive work strategies in the digital economy era.